The Role of Natural Gas in a Low-Carbon Europe: Infrastructure and Supply Security - Franziska Holz; Philipp M. Richter; Ruud Egging (The Energy Journal, 2016)
In this paper, we analyse infrastructure needs of the European natural gas market in response to decarbonisation of the European energy system. To this end, we use numerical modelling and apply the Global Gas Model. We investigate three pathways of future natural gas consumption: i) a decreasing natural gas consumption, following the scenarios of the EU Energy Roadmap 2050; ii) a moderate increase of natural gas consumption, along the lines of the IEA's New Policies Scenario; and iii) a temporary increase of natural gas use as a "bridge" technology, followed by a strong decrease after 2030. Our results show that current import infrastructure and intra-European transit capacity are sufficient to accommodate future import needs in all scenarios. This is despite a pronounced reduction of domestic production and a strong increase in import dependency. However, due to strong demand in Asia, Europe must increasingly rely on exports from Africa and the Caspian region, leading to new infrastructure capacity from these regions. When natural gas serves as a "bridge" technology, short-term utilisation rates of LNG import capacity temporarily increase instead of instigating large scale pipeline expansions.
Keywords: Q35; Q42; Q41; Q38; 330; Natural gas; Europe; Decarbonisation; Infrastructure